Electoral behaviour in the Peruvian Southern Andes facing the candidacies of the Lima Criollo elite, 1980-2021 - Nureña, César R. (2022)
Previous analysis of Peruvian presidential elections show that some candidates associated with the Criollo or Lima elites have received scant support in the southern Andean departments, where electoral preferences have been oriented instead to candidacies perceived as the most opposed to those elites. This study expands the scope of these approaches based on a historical-anthropological conceptual model referred to the elite of the Criollo ethnic group, which was used to identify 25 candidates from this social segment who have run for the presidency of the republic from 1980 to 2021. Statistical analyzes of the aggregate results at the provincial level of eight elections (in their first rounds) show that, indeed, it is possible to distinguish an ethnic voting phenomenon that is expressed as a rejection of the political options associated with the Criollo elite of Lima, defining a consistent and longitudinal pattern in all the elections included in the analysis. This phenomenon is observed in general in many Andean provinces, but it is stronger in those of the Southern Andes and acquires even greater intensity in the provinces with the highest proportions of Quechua and Aimara populations.